ANALYSIS OF REACT-BASED TEACHING MATERIAL TO IMPROVE STUDENTS’ SCIENCE PROCESS SKILLS IN ACID-BASE TOPIC - Afni, Khairul; Budiyanto, Mohammad; Isnawati, Isnawati (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2026)
This study aims to develop REACT-based teaching materials to improve students' Science Process Skills (SPS) in acid-base material. The main issues raised are the low achievement of junior high school students' SPS and the lack of contextual and inquiry-based learning approaches. The method used is qualitative descriptive, involving 20 ninth-grade students at PP. Sabilul Mukminin. Data were collected through observation, documentation, interviews, and student worksheets measuring five SPS indicators: classification, measurement, communication, prediction, and inference. The results showed that students' KPS scores were low to very low (17.50–48.00). The main obstacles included teacher-centered learning, minimal inquiry experiments, limited laboratory equipment, and the dominance of rote learning methods. These conditions limited students' involvement in the scientific thinking process. The REACT approach (Relating, Experiencing, Applying, Cooperating, Transferring) is proposed as a solution to create more meaningful and contextual science learning. The study recommends the development of REACT-based teaching materials as an effort to improve the quality of science education in schools.